Оцінка якості яблучних соків польських марок - Бліщ, Р. О.; Дзіняк, Б. О.; Кіріченко, К. С.; Blishch, R. O.; Dzinyak, B. O.; Kirichenko, K. S. (Lviv Politechnic Publishing House, 2005)
Висвітлено дослідження, спрямовані на визначення якості соків нефільтрованих польських виробників. Оцінка якості соків була основана на сенсорному аналізі та визначенні фізико-хімічних властивостей, а саме: густини, загального вмісту екстракту, кислотності. Дегустаційну оцінку якості соків здійснювали за п’ятибальною шкалою, на основі якої визначили рівень якості комплексним методом, що враховує вагомість окремих показників у загальній якості товару. Встановлено, що якість неосвітлених соків висока, що пояснюється легкою пастеризацією і відсутністю процесу освітлення.

In the work, research was conducted aimed at determining the quality of juices from unfiltered Polish producers. The evaluation of juice quality was based on sensory analysis and determination of physicochemical properties, namely: density, total extract content, acidity. The tasting assessment of juice quality was carried out on a 5-point scale, on the basis of which the quality level was calculated using a complex method that takes into account the importance of individual indicators in the overall quality of the product. It has been established that unclarified juices are of high quality, which is due to easy pasteurization and the absence of the clarification process.
Study of apple juices the quality of polish producer
Keywords: соки нефільтровані; концентровані соки; яблучні соки; технологія; пастеризація; juices; unfiltered concentrated juices; apple juices; technology